Implementation of Digital-Based Public Service Policy in Local Government: A Case Study of the Integrated Service Application - Sugiyanto, Hery; Apriza, Tiyas; Sopyan, Ence (JURNAL SOSIAL DAN HUMANIS SAINS, 2023)
This study examines the implementation of the Integrated Service Application (ISA) as a digital-based public service policy in an Indonesian local government. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that ISA has significantly improved administrative efficiency, reduced bureaucratic layers, and enhanced service accessibility for citizens. However, the study also identified challenges such as limited digital literacy among users, infrastructure constraints, and underutilized feedback mechanisms. Institutional leadership, regulatory frameworks, and interdepartmental coordination were found to be critical factors in the successful adoption of ISA. The study concludes that while digital innovation can transform public service delivery, it must be accompanied by strategic planning, inclusive digital education, and robust system support. These insights offer practical implications for other local governments aiming to modernize their public service systems through digital transformation.